Computed Tomography Estimation of Cochlear Duct Length Can Predict Full Insertion in Cochlear Implantation. Issue 3 (March 2016) - Johnston, James D. A.; Scoffings, Daniel; Chung, Mark; Baguley, David; Donnelly, Neil P.; Axon, Patrick R.; Gray, Roger F.; Tysome, James R.
Abstract : Objective: To compare the rates of full insertion of electrodes and hearing outcomes obtained with 28-mm and 31-mm cochlear implant electrode arrays. To assess whether cochlear duct length (CDL) estimated by preoperative computed tomography (CT) predicts whether an electrode is fully inserted. Study Design: A cohort study compared electrodes inserted and hearing outcomes after implantation with 28-mm or 31-mm arrays. CDL estimated from preoperative CT was compared in patients in whom full insertion of the 28-mm array was achieved compared with patients in whom at least one basal electrode was outside the cochlea. Setting: Tertiary referral cochlear implantation center. Patients: One hundred forty-eight patients implanted with 28-mm cochlear implant arrays (175 devices) and 74 patients implanted with 31-mm arrays (88 devices). Intervention: Cochlear implantation with 28-mm or 31-mm array. Main Outcome Measures: : Active electrodes at first programming, and at subsequent follow-ups. Bamford–Kowal–Bench sentence and auditory speech sound evaluation test results at 2 to 3 months in adult patients. CDL predicted by preoperative CT. Results: There was no difference in full insertion between the 28-mm and 31-mm array cohorts ( p = 0.22). Early hearing outcomes at 2 to 3 months showed no difference in mean auditory speech sound evaluation ( p = 0.19) or Bamford–Kowal–Bench results ( p = 0.853) between the 28-mm and 31-mm cohorts. CDL was shorter in the 22 patients with less than full insertion of the array with a mean length of 28.7 mm compared with 29.6 mm in the 42 patients in whom full insertion was achieved ( p = 0.046). Conclusion: CT estimation of CDL predicts full insertion after cochlear implantation. Insertion depth does not affect early hearing outcome.